VD_FINDINFO HC / 2014 / 391 vom 1. Mai 2014 - VD Tribunal cantonal (2014)
FRAIS JUDICIAIRES, DÉPENS, TRANSACTION JUDICIAIRE, ÉQUITÉ | 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 107 al. 1 let. c CPC (CH), 107 al. 1 let. f CPC (CH)